SEMIOTIKA DALAM LIRIK LAGU ‘AL BARQ AL YAMANI’ OLEH NISSA SABYAN DAN ADAM ALI - Al-Falah, Adib; Kuswardono, Singgih; Irawati, Retno Purnama (Universitas Negeri Semarang, 2021)
Song lyrics are basically part of literary works, they belong to poetry type literary works because both have similarities in their elements. So the analysis of the meaning of the lyrics of the song Al Barq Al Yamani which was popularized by Nissa Sabyan and Adam Ali is carried out using a semiotic analysis of Michael Riffaterre's model which focuses on poetry analysis (song lyrics). This study aims to find the meaning ofsong lyrics Al Barq Al Yamani's by describing (1) the unsustainability of the expression, (2) heuristic reading, (3) hermeneutic reading, (4) matrix, model and variant, and (5) hypogram. This research is a descriptive-qualitative research with a semiotic approach and the lyrics of the song Al Barq Al Yamani as its corpus. The design used in this research is library research.The results of this study are as follows. (1) the continuity of expressions includes: (a) displacing of meaning shown through the use of personified figurative language, metaphor and synecdiction, (b) distorsing of meaning through ambiguity and nonsense, (c) creating of meaning caused by rhyme, enjambement and typography (2) The heuristic reading describes the longing and desires of a person (writer) for his lover. (3) Hermeneutic reading describes the longing and desires of a person (writer) for his lover, namely the Prophet Muhammad SAW. A depiction of longing to meet and hope to be by his side. (4) Matrix: Prophet Muhammad SAW, model: longings and desires, as well as variants that spread throughout the verse. (5) Hypogram consists of potential and actual hypograms